Transcription factor Lhx2 is necessary and sufficient to suppress astrogliogenesis and promote neurogenesis in the developing hippocampus - Subramanian, Lakshmi (National Academy of Sciences, 2011)
The sequential production of neurons and astrocytes from neuroepithelial precursors is a fundamental feature of central nervous system development. We report that LIM-homeodomain (LIM-HD) transcription factor Lhx2 regulates this transition in the developing hippocampus. Disrupting Lhx2 function in the embryonic hippocampus by in utero electroporation and in organotypic slice culture caused the premature production of astrocytes at stages when neurons are normally generated. Lhx2 function is therefore necessary to suppress astrogliogenesis during the neurogenic period. Furthermore, Lhx2 overexpression was sufficient to suppress astrogliogenesis and prolong the neurogenic period. We provide evidence that Lhx2 overexpression can counteract the instructive astrogliogenic effect of Notch activation. Lhx2 overexpression was also able to override and suppress the activation of the GFAP promoter by Nfia, a Notch-regulated transcription factor that is required for gliogenesis. Thus, Lhx2 appears to act as a “brake” on Notch/Nfia-mediated astrogliogenesis. This critical role for Lhx2 is spatially restricted to the hippocampus, because loss of Lhx2 function in the neocortex did not result in premature astrogliogenesis at the expense of neurogenesis. Our results therefore place Lhx2 as a central regulator of the neuron-glia cell fate decision in the hippocampus and reveal a striking regional specificity of this fundamental function within the dorsal telencephalon.